Preliminary investigations in the synthesis of epoxidized natural rubber based conducting polymer / Chan Chin Han - Chan, Chin Han (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2006)
The electrical conductivity and glass transition temperature of epoxidized natural rubber / polyethylene oxide) (ENR/PEO) blends and ENR/PEO blends doped with lithium perchlorate (UCIO4) have been investigated by using solution casting method. Conductivities {a) of the solid polymer electrolyte films were measured by impedance spectrometer and glass transition temperatures (rgs) were measured by differential scanning calorimetry. ENR/PEO 40/60 shows the highest ionic conductivities at (4.02± 0.02) x 10"8 S/cm. Afterwards, ENR/PEO 40/60 was doped with various wt % of LiC104. 12 wt % of UCIO4 relative to the dry weight of polymer film shows the highest conductivity for ENR/PEO 40/60 blends at (1600 ± 100) x 10"8 S/cm. The T% for pure PEO is found at -54 °C, and the Ts for pure ENR is found at -19 °C. The addition of LiC104 salts in ENR/PEO blends causes the increases of T% for PEO and ENR.